Salivary biochemical markers as potential acute toxicity parameters for acute radiation injury: A study on small experimental animals. (March 2016) - Soni, S; Agrawal, P; Kumar, N; Mittal, G; Nishad, DK; Chaudhury, NK; Bhatnagar, A; Basu, M; Chhillar, N
Researchers have been evaluating several biodosimetric/screening approaches to assess acute radiation injury, related to mass causality. Keeping in mind this background, we hypothesized that effect of whole-body irradiation in single fraction in graded doses can affect the secretion of various salivary components that could be used as acute radiation injury/toxicity marker, which can be used in screening of large population at the time of nuclear accidents/disaster. Thirty Sprague Dawley rats treated with whole-body cobalt-60 gamma irradiation of dose 1–5 Gy (dose rate: 0.95 Gy/min) were included in this study. Whole mixed saliva was collected from all animals before and after radiation up to 72 h postradiation. Saliva was analyzed for electrolytes, total protein, urea, and amylase. Intragroup comparison of salivary parameters at different radiation doses showed significant differences. Potassium was significantly increased as the dose increased from 1 Gy to 5 Gy ( p < 0.01) with effect size of difference ( r > 0.5). Sodium was significantly altered after 3–5 Gy ( p < 0.01, r > 0.5), except 1 and 2 Gy, whereas changes in sodium level were nonsignificant ( p > 0.5). Urea, total protein, and amylase levels were also significantly increased as the radiation dose increased ( p < 0.01) with large effect size of difference ( r > 0.5). This study suggests that salivary parameters were sensitive toward radiation even at low radiation dose which can be used as a predictor of radiation injury.